An Analytical Approach to Optical Burst Switched Networks - Venkatesh, T.; Murthy, C. Siva Ram.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Optical burst switching (OBS) is envisioned to be one of the promising technologies to support bandwidth-intensive applications in the future Internet. An Analytical Approach to Optical Burst Switched Networks discusses architectures such as SOBS, SynOBS, HiTSOBS and applications of OBS networks in grid computing in metropolitan and access networks. The chapters in the book cover topics including models for the burst traffic considering the self-similar input traffic, models for the blocking probability with limited degrees of wavelength conversion, models for the performance of a network with deflection routing and segmentation capability and stochastic models for the performance of the TCP over OBS networks. The book$1 (Bs art material on modeling and analysis of OBS networks also helps the reader to gain a broader understanding of these networks. An Analytical Approach to Optical Burst Switched Networks provides extensive and up-to-date coverage on various aspects of OBS. The material is useful for researchers working in the area of high speed networks.s
to Optical Burst Switching -- Traffic Characteristics in OBS Networks -- Blocking Probability in OBS Networks -- Contention Resolution in OBS Networks -- TCP over OBS Networks.
Keywords: Engineering; Computer communication systems; Microwaves; Optical engineering; Electrical engineering; Engineering; Communications Engineering, Networks; Computer Communication Networks; Microwaves, RF and Optical Engineering; Electronic books